The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/s1677-5538.ibju.2016.0584
|View full text |Cite
|
Sign up to set email alerts
|

Long-term response of different Botulinum toxins in refractory neurogenic detrusor overactivity due to spinal cord injury

Abstract: Purpose To assess the response in spinal cord injured patients alternatively treated with different types and dosages of Botulinum neurotoxin type A (BoNT/A) over 15 years.Material and methods Patients who underwent first BoNT/A from 1999-2001 and practiced intermittent catheterization were included. Baseline 3-day bladder diary (BD) and urodynamics were collected. BoNT/A failure was defined when patients asked for re-injection ≤ 3 months post-treatment. Criteria for re-injection was at least one daily episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Previous studies had reported that a high baseline Pdet.max can usually predict poor urodynamic outcomes, whereas low bladder compliance was a predictor of failure after detrusor Botox injection [26,27]. Similarly, the current study found patients with a high Pdet and higher BCI and BOOI displayed marked improvement in urinary incontinence after detrusor Botox injection.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies had reported that a high baseline Pdet.max can usually predict poor urodynamic outcomes, whereas low bladder compliance was a predictor of failure after detrusor Botox injection [26,27]. Similarly, the current study found patients with a high Pdet and higher BCI and BOOI displayed marked improvement in urinary incontinence after detrusor Botox injection.…”
Section: Discussionsupporting
confidence: 78%
“…The persistence of the therapeutic effect after a single BoN-A injection in patients with LUTDs has varied among studies. In a study comparing the different types of BoNT-A injection for patients with neurogenic detrusor overactivity, approximately half of the patients (53.4%) exhibited continence at three months postinjection [74]. The mean interval of on-demand repeated injection was eight months, and no significant differences were found among types of BoNT-A injections.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study compared onabotulinumtoxinA with abobotulinumtoxinA for NDO showed that sustainable long-tern outcomes were achieved following both treatments. However, if the efficacy was not satisfactory, switching to another type of BoNT-A did not improve the response [ 65 ].…”
Section: T He Efficacy Of Repeated Injection Of Botulinum Toxin Type Amentioning
confidence: 99%